Selective impairment of platelet activation to collagen in the absence of GATA1. - Hughan, S; Senis, Y; Best, D; Thomas, A; Frampton, J; Vyas, P; Watson, S (2005)
Defects in the X-linked DNA-binding megakaryocyte transcription factor GATA1 cause thrombocytopenia and abnormal platelet function. However, detailed studies of GATA1 function in platelet activation are lacking. Here, we studied platelets from GATA1-deficient mice and from a male patient (S14) with a bleeding diathesis attributed to a single amino acid substitution (R216Q) in the N-terminal GATA1 zinc finger that alters binding to DNA. In both cases there was inhibition of aggregation to collagen and decreased tyrosine phosphorylation of glycoprotein VI (GPVI)-signaling proteins. This effect was more marked in GATA1-deficient murine platelets, where it was associated with a significant reduction in surface GPVI expression. Moreover, both human and murine GATA1-mutant platelets showed reduced adhesion and aggregate formation on a collagen matrix at an intermediate rate of shear, although this could not be accounted solely by the thrombocytopenia and altered GPVI expression, indicating that GATA1 regulates additional factors important for platelet activation under shear. In contrast, there was no inhibition of responses to G protein-coupled receptor agonists in GATA1-perturbed platelets. Our results are consistent with GATA1 regulating some but not all pathways of platelet activation, leading to an impairment of aggregate formation under flow, which cannot be attributed solely to the thrombocytopenia.